Sleep and physical activity: results from a long-term actigraphy study in adolescents - Castiglione-Fontanellaz, Chiara; Timmers, Tammy T.; Lerch, Stefan; Hamann, Christoph; Kaess, Michael; Tarokh, Leila (BMC public health, 2022)
Research to date suggests that physical activity is associated with improved sleep, but studies have predominantly relied on self-report measures and have not accounted for school day/free day variability. To address these gaps in the literature, the aim of the present study was to (a) quantify physical activity in adolescents using long-term daily actigraphy measurement and (b) to examine the association between actigraphically assessed steps and sleep behavior in a sample of healthy adolescents. To be able to capture intra- and inter-individual differences in the daily physical activity of adolescents, we examined within as well as between subjects effects and its association with sleep.
Gesehen am 11.08.2022